Education provided by the peritoneal dialysis nursing professional - Gomez Palma, Yoselin Irina Yubicsa (2021)
Peritoneal dialysis (PD) is an intracorporeal procedure that replaces kidney function; it is carried out by the patient or family member; Hence, the education given by the nursing professional is vital during this processbecause its purpose is to share knowledge in an organized manner, develop correct attitudes and habits that must be incorporated into their lifestyle. Objective: Describe and analyze the perception of Peritoneal Dialysis patients on the education provided by the professional of an EsSalud Hospital, 2020. Method: Qualitative research with a case study approach, the study subjects were 6 dialysis patients peritoneal of an Essalud hospital and 6 relatives, the sample was obtained by saturation and redundancy and the sampling was non-probabilistic. To collect data, a semi-structured interview guide was used, which was developed virtually respecting the criteria of scientific and ethical rigor. Main results: I: Nursing education, a  fundamental pillar in the development of PD. II: Attitude of the nursing professional towards the education provided in peritoneal dialysis, III: Participation of the patient and family caregiver in the education provided by the nursing professional, IV: Optimization of the lifestyle of peritoneal dialysis patients with the education provided by the nursing professional. Overall conclusion: The education provided by the nursing professional in peritoneal dialysis is recognized by patients and their families as the fundamental pillarfor increasing knowledge and skills before and during the procedure..